Ad-hoc Security Initiatives, an African response to insecurity. Issue 4 (2nd October 2022) - de Coning, Cedric; Yaw Tchie, Andrew E.; Grand, Anab Ovidie
ABSTRACT: This article contends that Ad-hoc Security Initiatives (ASI) have developed over the last decade in the Sahel and Lake Chad Basin and represents a new form of African collective security mechanism. The G5 Sahel Force and the Multi-National Joint Task Force emerged from a context-specific need for small clusters of African states to respond collectively to a shared cross-border security threat(s). The existing African Peace and Security Architecture (APSA) mechanisms were not specific and responsive enough to meet this emerging need. Despite substantial investments over the last twenty years by the African Union, Regional Economic Community/ Regional Mechanisms and international partners to establish the African Standby Force, this instrument was not agile enough to respond to the type of threats experienced in the greater Sahel region. In this article, we trace the emergence of a new type of ASI, examine how they fill an essential gap and analyse why the African Standby Force was not able to meet this need. We then consider the implications of these developments for the future of the APSA and how closer collaboration between ASIs and APSA can be developed.